Regulation of HCN Channels by Protein Interactions - Peters, Colin H.; Singh, Rohit K.; Bankston, John R.; Proenza, Catherine (Frontiers in Physiology, 2022)
Hyperpolarization activated, cyclic nucleotide-sensitive (HCN) channels are key regulators of subthreshold membrane potentials in excitable cells. The four mammalian HCN channel isoforms, HCN1-HCN4, are expressed throughout the body, where they contribute to diverse physiological processes including cardiac pacemaking, sleep-wakefulness cycles, memory, and somatic sensation. While all HCN channel isoforms produce currents when expressed by themselves, an emerging list of protein interacting partners shape HCN channel excitability to influence the physiologically relevant output. The best studied of these regulators is the auxiliary subunit, TRIP8b, which binds to multiple sites in the C-terminus to increase HCN channel expression and disrupt cAMP binding to fine-tune neuronal HCN channel excitability. Less is known about the mechanisms of action of other HCN channel interaction partners like filamin A, Src tyrosine kinase, and MinK-related peptides, which have a range of effects on HCN channel gating and expression. More recently, the inositol trisphosphate receptor-associated cGMP-kinase substrates IRAG1 and IRAG2 (also known as LRMP), were discovered as specific regulators of the HCN4 isoform. This review summarizes the known protein interacting partners of HCN channels and their mechanisms of action and identifies gaps in our knowledge.